2021
DOI: 10.14393/rcg228456771
|View full text |Cite
|
Sign up to set email alerts
|

Cobertura Jornalística Do Perigo Climático (Seca) 2012-2015 Na Bahia: Entre O Combate E a Convivência Com a Seca

Abstract: Entre os anos de 2012 a 2015, o Brasil enfrentou uma condição de seca plurianual, atingindo diversos setores da sociedade civil. A redução da disponibilidade de água, especialmente no semiárido baiano, colocou em evidência as políticas hídricas públicas realizadas na Bahia, estado localizado na região Nordeste do Brasil. Nesse mesmo quadriênio crítico, em termos de baixas precipitações, os jornais locais realizaram a cobertura desse importante evento climático. O presente trabalho é baseado nas matérias public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The fight against drought is a climatological misconception (SÃO JOSÉ et al,2021), considering that human beings do not control the climate phenomenon (SÃO JOSÉ, 2019;CONTI, 2011). Drought depends on macroscale factors, including the ocean-atmosphere interaction (CONTI, 2011), in such a way it cannot be fought by humankind.…”
Section: Brazilian Semiaridmentioning
confidence: 99%
See 2 more Smart Citations
“…The fight against drought is a climatological misconception (SÃO JOSÉ et al,2021), considering that human beings do not control the climate phenomenon (SÃO JOSÉ, 2019;CONTI, 2011). Drought depends on macroscale factors, including the ocean-atmosphere interaction (CONTI, 2011), in such a way it cannot be fought by humankind.…”
Section: Brazilian Semiaridmentioning
confidence: 99%
“…Nonetheless, it was in the first half of the 20 th century that critical views about the structural causes and consequences of regional poverty emerged, demystifying actions to fight drought. Meanwhile, São José ( 2019) and São José et al (2021) concluded that this paradigm is still in political use and in the imagery of the population.…”
Section: The Need For a New Perspective Of The Brazilian Semiaridmentioning
confidence: 99%
See 1 more Smart Citation